Pengaruh PDRB dan Tingkat Suku Bunga Riil Terhadap Permintaan Kredit Investasi Pada Bank Umum di Provinsi Bali Periode 2014-2018 - I Kadek Yoga Riantara; Putu Ngurah Suyatna Yasa; A. A Sri Purnami (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2022)
Investment loans are loans that are used by the public for the purchase or financing of capital goods in the context of building new projects, modernization. Where investment credit in the Province Bali in 2014 to 2018 has fluctuated every year. The purpose of this study is to determine the GRDP and the real interest rates on demand for investment credit simultaneously and partially at commercial banks in the Province of Bali. Data analysis used assumptions of classical from the F test sig. 0,000 < 0,05 which means that simultaneously obtained GDP variable and real interest rates significantly influence investment loans demand. From the t test on the GRDP variable has a positive and significant effect on the demand for investment loans, from the t on the variable real interest rate have a negative and significant effect on the demand for investment loans.